Association of HLA Class I Genotypes With Severity of Coronavirus Disease-19 - Shkurnikov, Maxim; Nersisyan, Stepan; Jankevic, Tatjana; Galatenko, Alexei; Gordeev, Ivan; Vechorko, Valery; Tonevitsky, Alexander (Frontiers in Immunology, 2021)
HLA class I molecules play a crucial role in the development of a specific immune response to viral infections by presenting viral peptides to cell surface where they will be further recognized by T cells. In the present manuscript we explored whether HLA class I genotype can be associated with critical course of COVID-19 by searching possible connections between genotypes of deceased patients and their age at death. HLA-A, HLA-B and HLA-C genotypes of n = 111 deceased patients with COVID-19 (Moscow, Russia) and n = 428 volunteers were identified with next-generation sequencing. Deceased patients were split into two groups according to age at death: n = 26 adult patients with age at death below 60 completed years and n = 85 elderly patients over 60. With the use of HLA class I genotypes we developed a risk score which is associated with the ability to present SARS-CoV-2 peptides by an individual's HLA class I molecule set. The resulting risk score was significantly higher in the group of deceased adults compared to elderly adults (p = 0.00348, AUC ROC = 0.68). In particular, presence of HLA-A*01:01 allele was associated with high risk, while HLA-A*02:01 and HLA-A*03:01 mainly contributed to the low risk. The analysis of homozygous patients highlighted the results even stronger: homozygosity by HLA-A*01:01 accompanied early deaths, while only one HLA-A*02:01 homozygote died before 60. Application of the constructed risk score model to the independent Spanish patients cohort (n = 45) revealed that the score is also associated with the severity of the disease. The obtained results suggest the important role of HLA class I peptide presentation in the development of a specific immune response to COVID-19.